Portable plaster smoothing machine / Muhammad Nur Helmi Mohd Mislim and Mohamad Hamdan Othman - Mohd Mislim, Muhammad Nur Helmi; Othman, Mohamad Hamdan (2023)
The study highlights the importance of prioritising consistency and quality in precast concrete construction using surface defect detection. Precast concrete offers numerous advantages in construction projects, with standardised components produced in a centralised plant using factory prefabrication. The aim of this research is to use surface defect detection to monitor precast concrete in terms of the material’s quality and consistency. The objective of this study is to focus on surface defect detection to enhance the consistency and quality of precast concrete components. By implementing a monitoring system that utilises advanced technologies, such as computer vision and image processing, defects in precast concrete elements can be detected and addressed at an early stage. This proactive approach mitigates the risk of compromised structural integrity, delays, and increased costs.